Congenital bone deformities and the inbred wolves (Canis lupus) of Isle Royale - Räikkönen, Jannikke; Vucetich, John A; Peterson, Rolf O.; Nelson, Michael P. (Biological Conservation, 2009)
The wolf (Canis lupus) population on Isle Royale, a remote island in Lake Superior, North America, is extremely inbred. Nevertheless, the consequences of genetic deterioration have not been detected for this intensively studied population, until now. We found that 58% (n = 36) of Isle Royale wolves exhibited some kind of congenital malformation in the lumbosacral region of the vertebral column and 33% exhibited a specific malformity, lumbosacral transitional vertebrae. By contrast, only 1% (1 of 99) of wolves sampled from two outbred, wolf populations exhibited this malformity. Moreover, in domestic dogs (Canis lupus familiaris) lumbosacral transitional vertebrae are associated with cauda equina syndrome, which can cause paresis, paralysis, locomotor difficulties in the rear legs and tail, and back pain. Whereas many studies illustrate how genetic deterioration affects population-level phenomena, such as survival and reproduction, these results are distinctive for demonstrating how genetic deterioration has compromised the morphology of individuals in a free-ranging population. The results are also significant because many policy makers and stakeholders and some conservation professionals use examples like Isle Royale wolves to downplay the consequences of genetic deterioration.